2014
DOI: 10.1186/1471-2407-14-63
|View full text |Cite
|
Sign up to set email alerts
|

Radical hysterectomy with adjuvant radiotherapy versus radical radiotherapy for FIGO stage IIB cervical cancer

Abstract: BackgroundThe goal of this study was to compare treatment outcomes for Federation of Gynecology and Obstetrics (FIGO) stage IIB cervical carcinoma patients receiving radical surgery followed by adjuvant postoperative radiotherapy versus radical radiotherapy.MethodsMedical records of FIGO stage IIB cervical cancer patients treated between July 2008 and December 2011 were retrospectively reviewed. A total of 148 patients underwent radical hysterectomy with pelvic lymph node dissection followed by adjuvant radiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 24 publications
0
29
1
2
Order By: Relevance
“…13 Chai et al showed that the incidence of severe lymphedema (grade 3-4, the National Cancer Institute Common Toxicity Criteria, Version 2.0) was significantly higher in the radical surgery with adjuvant radiotherapy group than in the primary radiotherapy group (6.76 vs. 2.07 %; P = 0.017). 14 The more prevalent and prolonged LEE and lymphedema in Group 1 in the current study might be explained by the synergistic effect of LND and radiotherapy on the advent of lower-limb lymphedema. LND directly damages the lymphatic system, resulting in lymphatic drainage disruption, and irradiation worsens this damage by accelerating fibrosis and preventing the formation of collateral circulation.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…13 Chai et al showed that the incidence of severe lymphedema (grade 3-4, the National Cancer Institute Common Toxicity Criteria, Version 2.0) was significantly higher in the radical surgery with adjuvant radiotherapy group than in the primary radiotherapy group (6.76 vs. 2.07 %; P = 0.017). 14 The more prevalent and prolonged LEE and lymphedema in Group 1 in the current study might be explained by the synergistic effect of LND and radiotherapy on the advent of lower-limb lymphedema. LND directly damages the lymphatic system, resulting in lymphatic drainage disruption, and irradiation worsens this damage by accelerating fibrosis and preventing the formation of collateral circulation.…”
Section: Discussionmentioning
confidence: 85%
“…13,14 Although not a primary outcome, several observational studies reported the differences in lower limb lymphedema among patients with FIGO stage IIB cervical cancer. Mabuchi et al showed that the incidence of severe lymphedema (grade 3-4, the National Cancer Institute Cancer Therapy Evaluation Program Common Terminology Criteria for Adverse Events, Version 2.0) was 5.3 % in the radical surgery with adjuvant radiotherapy group and 2.1 % in the primary radiotherapy group.…”
Section: Discussionmentioning
confidence: 99%
“…A decision-tree model to compare the cost and effectiveness between two primary treatment modalities for FIGO stage IIB cervical cancer patients was constructed using TreeAge Pro software (TreeAge Software Inc., Williamstown, MA, USA) ( Figure 1 ). Treatment arms were compared as defined by Chai et al 5 Surgery-based treatment arm contained 148 patients and consisted of radical hysterectomy combined with adjuvant external beam radiotherapy (EBRT) (1.8 or 2 Gy per fraction, with five fractions administered per week for a total of 25 fractions and 45–50 Gy). Of these patients, 69 patients (46.62%) had one or more risk factors and received TP (paclitaxel and cisplatin) regimen for four cycles.…”
Section: Methodsmentioning
confidence: 99%
“… 2 – 4 Our previous literature reported that radical radiotherapy was associated with fewer treatment-related complications and achieved a comparable survival outcome compared to radical hysterectomy plus adjuvant radiotherapy for FIGO stage IIB disease. 5 However, all the previous studies reported only progression-free survival, OS, or toxicities, whereas the costs of treatment have rarely been addressed.…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, the International Federation of Gynecology and Obstetrics(FIGO) approved the amendment staging system based on cutting-edge researches and discussed the management of cervical cancer based on the system. Although the preferred treatment is surgery, including multiple styles in the early stages [5], radiotherapy has the same effect in local control and survival for patients with contraindications to surgery or anesthesia [8][9][10]. As for locally advanced cervical cancer, concurrent chemoradiotherapy (CCRT) became the recommended treatment following 1999 National Cancer Institute report [5].…”
Section: Introductionmentioning
confidence: 99%